DADAISME: NOVEL PSIKOLOGIS - Th. Sri Rahayu Prihatmi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
Dadaisme is a story about people who are insane. They do repression and resistance. Nedena, Aleda’s patient, represses her terrible experience by closing communication, so that she becomes dumb. As a dumb person she does resistance, and so does Flo, Magnos patient. Tragically as psychoanalysts Aleda and Magnos undergo serious psychological problems. They are twins who love each other deeply. One of their twin sons – Jing – becomes a terrible psychopath: he enjoys seeing blood and hearing the screams of people who become the casualties of bomb explotion is a supermarket. It is such enjoyment which leads him to cruel section so that he explodes a supermarket. He also wants to take revenged his mother because she ‘abandons’ him. He wants to kill her. The complicated problems are arranged in a plot which is like a mosaic between past and present to trace the casually related events. The second person’s point of view is used as a technique to accuse the character. The title itself – Dadaisme- refers to the novel’s resistance towards the established ‘ism’ in literature, and denies traditional values.